Legal culture as a factor in the development of legal system - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article deals with the nature and the role of legal culture in the structure of legal system and its relationship with other components of legal system. The author comes to the conclusion that legal culture is an important factor in the development of legal system that affects legal awareness, law, legal relationship, law and order, lawmaking, law enforcement and other legal activities; and it is also a qualitative characteristic of legal system and the level of its excellence. The issues of legal culture in the formation of legal system are relevant to the current stage of development of national statehood and are conceptually important for theoretical legal research. The purpose of the scientific paper is to investigate the nature and the role of legal culture in the structure of legal system and to determine its relationship with other components of legal system. Legal culture is one of the important elements of legal system. Legal system interacts with the political, economic and cultural spheres of public life, and the result of the interaction of law and culture is legal culture, which is the system of beliefs, ideas, which determine the behavior and activities of people in legal sphere. Legal system and legal culture are closely connected, as the basis of their unity is guaranteed by the unity of legal provisions and legal behavior, which achieves social activity of law. Legal culture is a characteristic of the quality of legal system, and it is also the qualitative characteristic of not only one but all legal phenomena. On the basis of the research we can argue that legal culture is an important factor in the development of Ukraine’s legal system, which ensures its operation and development. For legal system, which is being transformed, it is important to improve and enhance the role of legal culture, develop a new system of legal values, provisions and principles, provide protection of rights, freedoms and legal interests of citizens. To assess the level of legal culture and legal system development the following criteria are required: social progress as the degree of freedom of natural rights, the degree of state guarantee of freedom and security of a person, the level of development of regulatory legal acts, legal activities, legal awareness, etc. Legal culture as a factor in the development of legal system should play a major role in the creation of a constitutional state, it is closely connected with all the elements of legal system, the formation of legal awareness of citizens, a new vision of the state as democratic, sovereign and independent, understanding the relationship of law and legislation, recognition of priority of a citizen’s role in legal relations, formation of legal values, which by their high-quality property contribute to legal sophistication of a person, positive nature of his legal activities, adequate assessment of legal reality, and real guarantee of the highest value – implementation of protection of human rights. This means that legal culture is one of the main factors of democratization of society that characterizes human behavior with regard to the level and content of his legal education, social activity, legal training and level of general education.